1985
DOI: 10.1016/s0092-8674(85)80034-9
|View full text |Cite
|
Sign up to set email alerts
|

Ribocharin: a nuclear Mr 40,000 protein specific to precursor particles of the large ribosomal subunit

Abstract: SummaryUsing a monoclonal antibody (No-194) we have identified, in Xenopus laevis and other amphibia, an acidic protein of M, 40,000 (ribocharin) which is specifically associated with the granular component of the nucleolus and nucleoplasmic 65S particles. These particles contain the nuclear 28S rRNA and apparently represent the precursor to the large ribosomal subunit in nucleocytoplasmic transit. By immunoelectron microscopy ribocharin has been localized in the granular component of the nucleolus and in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 58 publications
4
50
0
1
Order By: Relevance
“…Recently, Hiigle et al [26] identified a nuclear/nucleolar Mr 40,000 protein in Xenopus laevis and other amphibia which appears to be specific to precursor particles of the large ribosomal subunit. This protein , which was named ribocharin, was specifically mapped to the granular component of the nucleolus and nucleoplasmic 65 S particles in amphibia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hiigle et al [26] identified a nuclear/nucleolar Mr 40,000 protein in Xenopus laevis and other amphibia which appears to be specific to precursor particles of the large ribosomal subunit. This protein , which was named ribocharin, was specifically mapped to the granular component of the nucleolus and nucleoplasmic 65 S particles in amphibia.…”
Section: Discussionmentioning
confidence: 99%
“…Because fractionation of isolated Xenopus oocyte nuclei by differential centrifugation leads to well-defined protein fractions characterized by specific nuclear components (cf. Hü gle et al, 1985;Kö hler et al, 1997; SchmidtZachmann et al, 1998), the distribution of protein NOH61 in such fractions from oocyte nuclei, egg extracts, and somatic cells was analyzed by immunoblotting with the NOH61-specific antibody (Figure 4). Antibody NOH61-5.1, which shows the strongest cross-reactivity with the Xenopus homo- logue, recognized its antigen in total oocyte nuclei as well as in the LSP and HSP fractions, indicating that protein NOH61 is a nuclear protein bound to relatively large structures, i.e., the nucleoli (LSP) and extranucleolar nucleoplasmic particles (HSP), respectively.…”
Section: Biochemical Characterization Of Protein Noh61mentioning
confidence: 99%
“…Subsequent fractionation of nuclear contents by differential centrifugation was performed as described in detail by Hü gle et al (1985), resulting in fractions termed "low-speed pellet" (LSP), "high-speed pellet" (HSP), and "high-speed supernatant" (HSS). The LSP fractions were cleared from yolk proteins by Freon extraction (Evans and Kay, 1991).…”
Section: Isolation and Fractionation Of Xenopus Oocyte Nuclei And Eggmentioning
confidence: 99%
See 2 more Smart Citations